A STRENGTHENING MADRASAH STUDENTS’ CREATIVITY OF NON-ACADEMIC ACHIEVEMENT IN LOMBOK INDONESIA - Ahyar, Ahyar (Jurnal Tatsqif, 2023)
Student achievement is often measured by report cards, even though students have a lot of potential for non-academic achievements that have not been widely disclosed and developed. It is the Madrasah Aliyah Negeri 2 Mataram that has placed a parallel between academic achievement and non-academic achievement so that the madrasah harvests achievements from these two aspects. For this reason, this study reveals how to strengthen non-academic achievement and its impact. Field research at MAN (State Islamic School) 2 Mataram Model uses descriptive qualitative analysis; data collection was conducted with interviews involving the Head of the Madrasah, teachers, and students as key informants, observation, and documentation elaboration. The results showed that strengthening non-academic achievements by forming creative groups, creative group innovations, building creative group hard work that is supported by an attitude of appreciating the heterogeneity of inputs; appreciating various potentials, uphold creativity, thus producing a variety of creative innovations such as hafiz hafizah, peer mentors, films, talk shows, presenters, entrepreneurial spirit and leadership.